The Influence of Foreign Investment on Natural Resource Development in Indonesia: Penelitian - Syamsu Rijal; Andi Caezar To Tadampali; Marhawati; Nur Arisah; Sri Hutami Adiningsih S (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of foreign investment on the development of natural resources (SDA) in Indonesia using a descriptive qualitative approach. Foreign investment plays an important role in driving economic growth through the provision of capital, technology, and job creation, especially in the mining, energy, and plantation sectors. However, behind its contribution, there are major challenges related to environmental sustainability, social inequality, and the dominance of control of natural resources by foreign parties. The data in this study were obtained through library research, document review, and analysis of relevant literature. The results of the study indicate that the development of natural resources involving foreign investment often does not fully prioritize the principles of social justice and ecological sustainability. Therefore, an active role is needed from the government, society, academics, and NGOs to ensure that foreign investment is not only economically profitable, but also fair and sustainable. This study recommends strengthening regulations, technology transfer, local community involvement, and increasing transparency in every process of natural resource investment.